Sutureless intrascleral fixation using different three‐piece posterior chamber intraocular lenses: a literature review of surgical techniques in cases of insufficient capsular support and a retrospective multicentre study. Issue 3 (1st December 2019) - Czajka, Marcin Piotr; Frajdenberg, Agata; Stopa, Marcin; Pabin, Tomasz; Johansson, Björn; Jakobsson, Gunnar
Abstract: We present a literature review of surgical techniques of intraocular lens placement in eyes with insufficient capsular support, focusing on the most recent publications, together with a retrospective multicentre consecutive case series analysis of 103 eyes undergoing pars plana vitrectomy and sutureless intrascleral (SIS) fixation of a standard three‐piece PCIOL. Many different approaches appear in the literature without any specific procedure achieving superior outcomes. Advantages and disadvantages vary between techniques. Common complications related to IOL fixation techniques were as follow: anterior chamber IOL: transient/permanent corneal oedema (9–66.6%), uveitis (1.1–39.3%); iris‐fixated IOL: pupil ovalization (16–47.7%); and sutured scleral‐fixated IOL: suture breakage/exposure (6.1–11%), vitreous haemorrhage: (5.5–16.6%). In our retrospective case series, indications for surgery were postoperative aphakia in 50 eyes (49%), IOL dislocation in 38 eyes (37%) and natural lens dislocation in 15 eyes (14%). Scleral tunnels for haptic fixation were created with (28 eyes, 27.2%) or without (75 eyes, 72.8%) 25 gauge trocar cannulas. Complications included transient hypotony ( n  = 20; 19.4%), corneal decompensation ( n  = 7; 6.7%), IOL dislocation ( n  = 6; 5.8%), cystoid macular oedema ( n  = 5; 4.8%), vitreous haemorrhage ( n  = 4; 3.8%) and retinal detachment ( n  = 4; 3.8%). Mean best corrected visual acuity improved from logMAR 0.65 to 0.36 at the final visit (p = 0.001). In conclusion, SIS fixation provides good anatomical and functional outcomes; however, complications can occur. The number of surgical approaches for IOL dislocation described in the literature indicates that optimal treatment remains to be found.